THE CULTURE OF CONSUMMATING SOCIETY AND SOLITUDE - Ігнатенко, І. В. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
The research observes the deformation of communication process. The phenomena of loneliness occurs as a result of communication’s gaps and new nature of postmodern society.